Emulating an atomic gyroscope with multiple accelerometers - Shettell, Nathan (2024)
The main advantage of an atomic accelerometer when compared to a classical accelerometer is negligible bias drift, allowing for stable long-term measurements, which opens the potential application in navigation. This negligible drift arises from the fact that the measurements can be traced back to natural constants, and the system is intrinsically stable due to the simple design. In this manuscript, we extend this property of long-term stability to gyroscopic measurements by considering an array of atomic accelerometers, and comparing the performance to atomic gyroscopes, which are technologically more prone to bias drifts. We demonstrate that an array consisting of four three-axis atomic accelerometers can outperform state of the art atomic gyroscopes with respect to long-term stability.